Examining priorities and investments made through the Global Financing Facility for maternal and newborn health: a sub-analysis on quality - Kumar, Meghan; Kinney, Mary; Kiendrébéogo, Joël; Shamba, Donat; Lawn, Joy E.; Waiswa, Peter (Global health action, 2024)
Improving quality of care could avert most of the 4.5 million maternal and neonatal deaths and stillbirths that occur each year. The Global Financing Facility (GFF) aims to catalyse the national scale-up of maternal and newborn health (MNH) interventions through focused investments. Achieving impact and value for money requires high, equitable coverage and high quality of interventions. This study examines whether the rhetoric of increasing coverage together with quality has informed investment strategies in MNH through a secondary analysis of 25 GFF documents from 11 African countries. The analysis shows that the country GFF-related documents incorporate some MNH-related quality of care components; however, there is a lack of clarity in what is meant by quality and the absence of core MNH quality of care components as identified by the World Health Organization’s MNH quality framework, especially experience of care and newborn care. Many of the Investment Cases have a more diagonal focus on MNH service delivery considering the clinical dimensions of quality, while the investments described in the Project Appraisal Documents are primarily on horizontal structural aspects of the health system strengthening environment. The GFF is at the forefront of investing in MNH globally and provides an important opportunity to explicitly link health systems investments and quality interventions within the MNH continuum of care for optimal impact. Main findings: The analysis of maternal and newborn health-related quality of care in Global Financing Facility country documents reveals variability in depth and content, with most documents focusing on horizontal approaches to health system strengthening and if specific to maternal and newborn health, the focus is on provision of quality maternal care with little to no attention on experience of care and quality newborn care.Added knowledge: This content analysis is the first to examine quality and maternal and newborn health within the content of Global Financing Facility documents showing that patient experience, stillbirths, and specific quality newborn indicators are seldom mentioned.Global health impact for policy and action: The analysis underscores the need for more diagonal approaches to address the highest impact interventions for maternal and newborn health and the need to focus on person-centered care within the Global Financing Facility related processes for the investment to have maximum impact. Main findings: The analysis of maternal and newborn health-related quality of care in Global Financing Facility country documents reveals variability in depth and content, with most documents focusing on horizontal approaches to health system strengthening and if specific to maternal and newborn health, the focus is on provision of quality maternal care with little to no attention on experience of care and quality newborn care. Added knowledge: This content analysis is the first to examine quality and maternal and newborn health within the content of Global Financing Facility documents showing that patient experience, stillbirths, and specific quality newborn indicators are seldom mentioned. Global health impact for policy and action: The analysis underscores the need for more diagonal approaches to address the highest impact interventions for maternal and newborn health and the need to focus on person-centered care within the Global Financing Facility related processes for the investment to have maximum impact.
Gesehen am 03.06.2025